Effect of Vitamin C on Blood Glucose & Serum Lipids in Type 2 Diabetes Patients - Nath, Ronjon Kumer; Akhter, Marufa; Sarker, Kali Rani; Rahman, Md Rezwanur; Chowdhury, Shahela Sultana; Ishrat, Rumana (KYAMC Journal, 2017)
Background & objectives: The prevalence of diabetes is rising at an alarming sign through out the world & is one of the major metabolic disorders that cause micro & macro-vascular complications. Dyslipidaemia is considered as risk factor for cardiovascular disease & it is higher risk in diabetes subjects than normal. The control of glycemic & lipid profile status can reduced the risk of micro & macro-vascular complications. As vitamin C is anti oxidant vitamins so we aimed to evaluate the beneficial effects of its on blood glucose & serum lipids in T2DM patients. Materials & methods: A total of 46 patients with T2DM were included in this study. They received 1000 mg of vitamin C for eight weeks. Fasting blood sugar (FBS), triglyceride (TG), total cholesterol (TC), low & high density lipoprotein (LDL & HDL) and glycated haemoglobin (HbA1c) were measured before & after vitamin consumption and the results were analyzed. Results: A significant decrease in TG, TC, LDL, and HbA1c was seen in the group supplemented with 1000 mg vitamin C. In case of FBG & HDL there was no significant difference. Interpretation & conclusions: Our results indicate that daily consumption of 1000 mg supplementary antioxidant vitamin-C may be beneficial in decreasing glycemic status and lipids in patients with type 2 diabetes and thus reducing the risk of complications. KYAMC Journal Vol. 4, No.-1, July 2013, Page 337-340